(3OjhGf GdRjhQj GdHZOGOjs - (3YHGS Hf GdbGSe Hf EHQGgje GdRjhQj GdUaGQ,J (B1315 (3g` s
(3ChdgG (B:s
(3JNejS GdbUjOI GdChdi ef gGTejGJ GdcejJ Ydb GdbdH HGdogOGI GdcQGe hLfG aj pUHGg hqUd GddFGe s
(3BNQgG (B:s
(3aGQMehfG EPG MddfG dOjce UdhGJ GdEdg JJQi Ydjce eG GSJOGQJ chGcH HSeGgG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B38 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B63s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B113 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHIBjI Gddg GdMcje GdYGeI HGdfLa (B(569) s
Keywords: (3GdCOHs